1995
DOI: 10.1002/lt.500010410
|View full text |Cite
|
Sign up to set email alerts
|

The role of tumor markers in the diagnosis of hepatocellular carcinoma, with special reference to the des-gamma-carboxy prothrombin

Abstract: The assessment of new and more sensitive serum markers for hepatocellular carcinoma (HCC) represents a useful contribution to the diagnosis of small liver tumors, still amenable by surgery. We evaluated the efficacy of the tumor markers proposed during recent years for the study of HCC: alpha fetoprotein (AFP), carcinoembryonic antigen (CEA), serum ferritin (SF), tissue polypeptide antigen (TPA), and, finally, the more recently proposed des-gamma-carboxy prothrombin (DCP). Of the 227 patients included in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 24 publications
2
64
0
Order By: Relevance
“…These results are in accordance with previous reports [3,8,10,12,[15][16][17][18][19][34][35][36] . However, limiting this to small hepatocellular carcinoma, DCP alone is the independent prognostic factor for both tumor recurrence and patients' survival, while presence of microscopic vascular invasion is a prognostic factor in patients outside the criteria.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…These results are in accordance with previous reports [3,8,10,12,[15][16][17][18][19][34][35][36] . However, limiting this to small hepatocellular carcinoma, DCP alone is the independent prognostic factor for both tumor recurrence and patients' survival, while presence of microscopic vascular invasion is a prognostic factor in patients outside the criteria.…”
Section: Discussionsupporting
confidence: 94%
“…Shirabe et al [8] reported that the preoperative DCP level, tumor diameter, and histologic differentiation correlated with the presence or absence of microscopic vascular invasion in a study on 218 patients who had undergone hepatic resection. Sakon et al [2] , Suehiro et al [4] , Grazi et al [3] , Sugimoto et al [5] , and Nanashima et al [13] also reported that a high preoperative DCP level correlated with the presence of microscopic vascular invasion in patients undergoing hepatectomy. Shimada et al [6] reported in a study on 40 patients who had undergone a living donor liver transplantation DCP levels ≥ 300 mAU/mL to be correlated with the presence of microscopic vascular invasion and DCP thus to be a poor prognostic factor.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Several investigations have made comparisons of the usefulness of DCP and AFP for HCC diagnosis [37][38][39][40]. However, whether AFP is superior to DCP in all cases is still controversial.…”
Section: Discussionmentioning
confidence: 99%